PEMBUATAN PORTOFOLIO DALAM PROSES PEMBELAJARAN BAHASA INDONESIA PADA ASPEK MENULIS DI SMA PERTIWI 1 PADANG - Zulfitriyani; Yulia Sri Hartati; Samsiarni (Kilau Publishing, 2023)
A portfolio learning strategy is a form of changing the mindset from teacher-centered to student-centered. This strategy is a learning innovation designed to help students understand theory in depth through practical-empirical learning experiences. A portfolio strategy can be an approach program that encourages competence, responsibility, and student participation, learns to assess and influence public policies, and dares to participate in activities between peers, between schools, and between members of the community. The results of the portfolio for the process of learning Indonesian in the writing aspect can be used in the learning process, especially in the Indonesian language subject at SMA 1 Pertiwi, Padang. This activity needs to be carried out as a follow-up service to training on developing Indonesian learning strategies for teachers because through this kind of activity teachers' insight and understanding will increase. Along with the demands of teacher professionalism, teachers must always improve their ability to manage learning. In addition, teachers also get new information related to the world of education.